Restructuring of State Ministry Authority: Fostering Efficiency Based on Lean Governance Principles - Arifin, Firdaus; Maarif, Ihsanul; Kurniati, Yeti; Bahri, Robi Asadul; Murbani, Anastasia Wahyu (Susbtantive Justice International Journal of Law, 2024)
The present study sets out to explore the application of lean governance principles to streamline state ministries' bureaucratic structures, with a focus on reducing waste and optimizing workflow. It is hypothesized that such an approach would enhance the responsiveness of public services, thereby addressing the inefficiencies in decision-making and resource wastage that are often observed in bloated bureaucratic structures, where ministries frequently have overlapping authority. A normative juridical research method was used to foster relevant regulations and assess the compatibility of the concept within the context of government administration. The findings indicate that lean governance can reduce redundancy and improve efficiency through authority restructuring, simplifying bureaucratic processes, and strengthened inter-agency coordination. The implications of this study include the need for regulatory adjustments to support authority restructuring and enhanced information technology to improve transparency and accountability. Consistent implementation of lean governance is expected to create a more responsive and adaptive government, ultimately fostering greater public trust in the public sector.